Testing the importance of jasmonate signalling in induction of plant defences upon cabbage aphid (Brevicoryne brassicae) attack - Kuśnierczyk, Anna; Tran, Diem HT; Winge, Per; Jørstad, Tommy S.; Reese, John C.; Troczyńska, Joanna; Bones, Atle M. (My University, 2012)
Background: Phloem-feeding aphids deprive plants of assimilates, but mostly manage to avoid causing themechanical tissue damage inflicted by chewing insects. Nevertheless, jasmonate signalling that is induced by infestation is important in mediating resistance to phloem feeders. Aphid attack induces the jasmonic acid signalling pathway, but very little is known about the specific impact jasmonates have on the expression of genes that respond to aphid attack. Results: We have evaluated the function that jasmonates have in regulating Arabidopsis thaliana responses to cabbage aphid (Brevicoryne brassicae) by conducting a large-scale transcriptional analysis of two mutants: aos, which is defective in jasmonate production, and fou2, which constitutively induces jasmonic acid biosynthesis. This analysis enabled us to determine which genes’ expression patterns depend on the jasmonic acid signalling pathway. We identified more than 200 genes whose expression in non-challenged plants depended on jasmonate levels and more than 800 genes that responded differently to infestation in aos and fou2 plants than in wt. Several aphid-induced changes were compromised in the aos mutant, particularly genes connected to regulation of transcription, defence responses and redox changes. Due to jasmonate-triggered pre-activation of fou2, its transcriptional profile in non-challenged plants mimicked the induction of defence responses in wt. Additional activation of fou2 upon aphid attack was therefore limited. Insect fitness experiments revealed that the physiological consequences of fou2 mutation contributed to more effective protection against B. brassicae. However, the observed resistance of the fou2 mutant was based on antibiotic rather than feeding deterrent properties of the mutant as indicated by an analysis of aphid feeding behaviour. Conclusions: Analysis of transcriptional profiles of wt, aos and fou2 plants revealed that the expression of more than 200 genes is dependent on jasmonate status, regardless of external stimuli. Moreover, the aphid-induced response of more than 800 transcripts is regulated by jasmonate signalling. Thus, in plants lacking jasmonates many of the defence-related responses induced by infestation in wt plants are impaired. Constant up-regulation of jasmonate signalling as evident in the fou2 mutant causes reduction in aphid population growth, likely as a result of antibiotic properties of fou2 plants. However, aos mutation does not seem to affect aphid performance when the density of B. brassicae populations on plants is low and aphids are free to move around.
Citation: Kuśnierczyk et al.: Testing the importance of jasmonate signalling in induction of plant defences upon cabbage aphid (Brevicoryne brassicae) attack. BMC Genomics 2011 12:423.
Keywords: Aphid; Gene expression; Infestation; Jasmonic acid signalling; Microarrays; Plant defence; EPG